Prevalence of Polycystic Ovarian Syndrome in Women of Reproductive Age in Mymensingh Region of Bangladesh – A Sonographic Evaluation (Community Based Medical Journal, 2025)
Polycystic ovarian syndrome (PCOS) is a common hormonal disorder affecting 5-15% of women of reproductive age. This cross-sectional study aims to provide a comprehensive understanding of the prevalence of PCOS in women of reproductive age leveraging sonographic evaluation. The study was conducted in the Department of Radiology & Imaging at Community-Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January and December of 2022. Inclusion criteria were women aged between 15 and 45 years with suspected signs and symptoms of PCOS. Those with menstrual irregularities, hirsutism, severe acne, or abnormal hormone levels were excluded. Finally, a total of 120 women were included in the study. Pelvic ultrasounds were performed using a Samsung Sonoace X7 machine with a 3.5 MHz transabdominal transducer. 15(12.5%) were diagnosed with PCOS, while 105(87.5%) were negative. The age distribution shows the most significant group is 21-25 years (46.67%), followed by 15-20 years (24.17%). BMI data reveals the majority are overweight (40.83%), with an average BMI of 31.67%, and fewer in underweight (11.67%), obese (14.17%), and morbidly obese categories (1.67%). Clinical presentations include primary infertility (24.17%), secondary infertility (20.83%), chronic anovulation (15.00%), and no cases of hirsutism. Follicular diameters and ovarian volume were measured using Sono-AVC and VOCAL (3D) methods, with two identified cystic patterns: peripheral and general. Based on sonographic evaluation, our study revealed 12.5% prevalence of PCOS, with higher prevalence in the 21-25 age groups in women of reproductive age in Mymensingh region of Bangladesh.  CBMJ 2025 January: Vol. 14 No. 01 P: 89-95